Evaluasi sistem pengelolaan limbah medis Puskesmas di wilayah Kabupaten Bantul - Riang Lala Manila; Sarto Sarto (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Evaluation of community health center's medical waste management system in Bantul RegencyPurposeThis study aimed to evaluate the Primary health centers medical waste management systems.MethodsThis research was a qualitative study using a case study design in five Puskesmas of Bantul District.ResultsThe management of medical waste in Bantul Regency is a new model using private party as a user (health cooperative) to hire services to the private transporter (CV. Jogya Prima Perkasa) to carry out the transportation and destruction of medical waste generated by health facilities of Puskesmas, Pustu, Polindes and private health facilities. Consideration of Health Cooperation is a private institution belonging to Dinas Kesehatan and has a legal entity considered more flexible to bail out the initially issued funds to pay the financing of transport and extermination services to the transporter.ConclusionPrimary health care medical waste management has followed the regulations. Health center has conducted medical waste management starting from the sorting, collection, packaging, storage, and transport. There should be improvements in some aspects, especially the creation of TPS for Puskesmas that do not have them yet, while Puskesmas who already have TPS need to make improvements according to the conditions specified.